fMRI adaptation reveals: the human mirror neuron system discriminates emotional valence - Schmidt, Stephanie N. L.; Sojer, Christian A.; Haß, Joachim; Kirsch, Peter; Mier, Daniela (Cortex, 2020)
Our ability to infer other individuals' emotions is central for successful social interactions. Based on the theory of embodied simulation, our mirror neuron system (MNS) provides the essential link between the observed facial configuration of another individual and our inference of the emotion by means of common neuronal activation. However, so far it is unknown, whether the MNS differentiates the valence of facial configurations. To increase the precision of our fMRI measurement, we used an adaptation design, which allows insights into whether the same neuronal population is active for subsequent stimuli of facial configurations. 76 participants were shown congruent, or incongruent consecutive pairs of facial configurations expressing fear or happiness. Significant activation for changes in emotional valence from adaptor to target was revealed in fusiform gyrus, superior temporal sulcus, amygdala, insula, inferior parietal lobe and Brodmann area 44. In addition, activation change was higher in superior temporal sulcus, insula and inferior frontal gyrus for a switch from happiness to fear than for fear to happiness. Our results suggest an involvement of the MNS in valence discrimination, and a higher sensitivity of the MNS to negative than positive valence. These findings point to a role of the MNS that goes beyond the mere coding of a motor state. (c) 2020 Elsevier Ltd. All rights reserved.